2020
DOI: 10.3389/fenvs.2020.00013
|View full text |Cite
|
Sign up to set email alerts
|

Cover Cropping May Alter Legacy Phosphorus Dynamics Under Long-Term Fertilizer Addition

Abstract: Use of cover crops in an integrated agricultural system can reduce demand of inorganic phosphorus (P) fertilizers, where the subsequent crops can take up P accumulated in cover crops biomass after the decomposition. In this research we hypothesized that some cover crops can take up P from less labile fractions and recycle it back to the soil through plant residues resulting in better P use efficiency of the system; cover crops are capable of P uptake from subsurface layers which leads to the accumulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…The analysis of spatial field data and survey data provided by the agricultural retailers about the farmer and their operation revealed important information about the history of elevated-P fields and some characteristics that could influence the rate of P-loss. With cover crops, for example, studies have shown that P is moved from the subsurface to the surface soil layer which could explain why this practice was associated with elevated-P in our study (Soltangheisi et al, 2020). Alternatively, farmers who were concerned that P concentrations were too high in their fields may have been more likely to plant cover crops or engage in other conservation practices, leading to the positive correlation.…”
Section: Discussionmentioning
confidence: 71%
“…The analysis of spatial field data and survey data provided by the agricultural retailers about the farmer and their operation revealed important information about the history of elevated-P fields and some characteristics that could influence the rate of P-loss. With cover crops, for example, studies have shown that P is moved from the subsurface to the surface soil layer which could explain why this practice was associated with elevated-P in our study (Soltangheisi et al, 2020). Alternatively, farmers who were concerned that P concentrations were too high in their fields may have been more likely to plant cover crops or engage in other conservation practices, leading to the positive correlation.…”
Section: Discussionmentioning
confidence: 71%
“…In the last years the adoption of cover cropping has been proposed as a feasible alternative to the costly and environmentally harmful conventional agronomic management in specialized orchards of Mediterranean agroecosystems 14,16 . The present work represents a step forward by elucidating the effect of T. subterraneum cover crop on the nutritional status of apricot trees as compared to both spontaneous flora cover cropping and conventional management (as a control).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the efforts of scientists are oriented for searching more sustainable management practices, aimed at enhancing yield and product quality of both herbaceous and arboreal crops, while at the same time optimizing the use of both external and internal chemical inputs 6–9 . In this framework, cover cropping (the mono‐ or inter‐cropping of herbaceous plants over either part of a year, or over an entire year) may provide important benefits to orchards, since it may reduce soil erosion and nutrient leaching, 10,11 keep the soil humidity at the proper level, 12 maintain soil fertility replenishing its organic matter, 13 enriching nitrogen (N) content (especially when leguminous cover crops are grown) 14 and releasing previously non‐available soil phosphorus (P) through the release of secondary metabolites into the rhizosphere 15,16 . In addition, cover crops also enhance soil microbial populations, encourage generalist predator arthropod populations and heartworm communities, and reduce pest and weed pressure 10,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…These species were able to mobilize labile and less labile Po and increase the proportion of Pi in the soil solution. Considering the literature on cover crop species, white lupine is widely suggested to be the most efficient for extracting Po and Pi forms and could be considered a P-mobilizing species, although this may depend on the characteristic of the organic input applied [209,210]. Furthermore, though there is little information available in the literature, it is also pointed out that cover crops could specifically increase the dissolution of resistant Po associated with fulvic acid and highly resistant Po associated with humic acid [211,212].…”
Section: Subterranean Clovermentioning
confidence: 99%